Reconstruction of wasatiyyah based Muslim civilization in ASIAN region - Hassan, Mohd. Kamal (2015)
Today the phenomenon of “social and moral turbulence” has gone beyond the boundaries of banking and finance to embrace global politics, climate change and environmental disasters, international relations, inter-religious and intra-religious discord, food insecurity scenario, urban crime, lawlessness, and – not least – the daily hazards of living in an environment, system or culture with low standards of moral integrity in many cities of the Muslim world. For the Muslim majority communities of Indonesia, Malaysia and Brunei Darussalam, and the Muslim minorities of the Philippines, Thailand, Singapore, Myanmar, Cambodia, Vietnam and Laos, the way the Islamic culture and civilization are going to develop in the context of ASEAN Economic Community of 2015 and beyond are going to be crucial for the survival of the Muslim ummah as a positive civilizing force. It is hoped that the formation of the ASEAN Community and its consolidation in the coming years would allow for greater public space for Muslim communities to play the role of Rahmatan Li’L-‘Alamin, (Mercy to all Mankind) and Ummatan Wasatan ( Justly Balanced Community) in a shared and enlarged economic and cultural environment, such that the presence of Islam and the Muslim community would be perceived by the non-Muslim communities in ASEAN as a force that represents the message of peace, mutual respect and cooperation with non-Muslim communities.